2013
DOI: 10.1182/blood-2012-07-442962
|View full text |Cite
|
Sign up to set email alerts
|

Notch controls generation and function of human effector CD8+ T cells

Abstract: Key Points Activation-induced Notch signaling is crucial for both generation and effector functions of primary naive CD8 T cells. Notch signaling is needed for expansion and IFNγ release but not for cytolytic activity of established effector CD8 T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…Furthermore, we found that expression of N1IC in antigen-specific CD8 + T cells promoted effector responses through amplification of canonical and non-canonical Notch pathways and rendered T cells resistant to tumor-induced tolerance. A similar promotion of T-cell cytotoxicity by Notch signaling was recently confirmed in human CD8 + T cells (32). In addition, signaling through Notch-2 promoted cytotoxic activity of CD8 + T cells (28), suggesting a similar effect of Notch-1 and -2 in CD8 + T-cell effector responses.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, we found that expression of N1IC in antigen-specific CD8 + T cells promoted effector responses through amplification of canonical and non-canonical Notch pathways and rendered T cells resistant to tumor-induced tolerance. A similar promotion of T-cell cytotoxicity by Notch signaling was recently confirmed in human CD8 + T cells (32). In addition, signaling through Notch-2 promoted cytotoxic activity of CD8 + T cells (28), suggesting a similar effect of Notch-1 and -2 in CD8 + T-cell effector responses.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, Jagged-1 expression suppressed collagen-induced arthritis by providing negative signals in CD8 + T cells (29). Interestingly, treatment of tumor-bearing mice with agonistic antibodies against Notch-2 or DLL1- or DLL4-Fc fusion proteins led to antitumor responses (30-32), suggesting the potential therapeutic effect of promoting Notch signaling in cancer. However, these therapeutic approaches were systemic and did not specifically target T cells.…”
Section: Introductionmentioning
confidence: 99%
“…+ T-cell immune responses (21,22) and cytokine/chemokine expression (23). The regulation of Notch1 and Tbx21 by EGR2 thus helps to explain the importance of EGR2 for a normal immune response to influenza.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the Notch receptor involved (Notch 1 or Notch 2) may vary depending on the experimental context. A recent study reported a role for Notch also in the generation and function of human CD8 + T cells, suggesting that its role in this particular subset of T cells is conserved 105 . Collectively, these experiments show an important role for Notch signalling in the differentiation of functional CTLs.…”
Section: Box 2 | Notch and Autoimmune Diseasementioning
confidence: 99%